The kinetics of transpassive dissolution chemistry of stainless steels in nitric acid: The impact of Si. (20th December 2017) - Laurent, Barbara; Gruet, Nathalie; Gwinner, Benoit; Miserque, Frederic; Rousseau, Karine; Ogle, Kevin
Abstract: Atomic emission spectroelectrochemistry was used to monitor the elemental dissolution of two stainless steels during transpassive polarization. A 304LN stainless steel (X2 CrNiN 18-10) was compared with a 3.5 wt% Si rich stainless steel (X1 CrNiSi 18-15-4) so as to elucidate the effect of Si on the dissolution mechanism. The enrichment in Si shifted the cathodic reaction to lower potentials explaining that in hot and concentrated nitric acid containing oxidizing species, 304LN SS corrodes more rapidly due to the transpassive break of passivity, while the 3.5 wt% Si SS remains passive. However, when polarized into the transpassive domain, preferential grain boundary corrosion was observed for the 304LN but not for the 3.5 wt% Si SS, despite having similar current densities. Congruent alloy dissolution was observed in the transpassive domain with the stoichiometry of Fe(III), Cr(VI) and Ni(II) yielding a faradaic yield of 100% at early times. For longer times, with the 304LN, the faradaic yield drop to 70% indicative of intergranular dissolution in which the cations released in the intergranular space were not detected by the ICP-AES. Transmission electron microscopy coupled with energy dispersive spectroscopy showed that the interface of the 3.5 wt% Si SS enriches in Cr during a polarization in the transpassive domain of the steel. No similar enrichment was detected for the 304LN. Graphical abstract: